2000
DOI: 10.1046/j.1365-2133.2000.03255.x
|View full text |Cite
|
Sign up to set email alerts
|

A sporadic case of progressive mucinous histiocytosis

Abstract: Hereditary progressive mucinous histiocytosis is a rare autosomal dominant non-Langerhans cell histiocytosis. We describe a sporadic case of this syndrome in a 64-year-old woman who had multiple dark-red dome-shaped papulonodules located mainly on the back of her hands, forearms and thighs. Light microscopy revealed a circumscribed upper dermal aggregate of ovoid or spindle-shaped histiocytes with abundant mucin deposition. Iron deposits and numerous mast cells were scattered throughout the tumour but giant ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 17 publications
1
35
1
Order By: Relevance
“…Staining with toluidine blue reveals a marked metachromasia of the histiocytic cells. In accordance with some authors, 53 immunohistochemical studies performed by us showed positive labeling of the histiocytic cells with KP1 (CD68), and factor XIIIa, but S-100 protein and CD1a were negative. In contrast, other investigators 50 found that the histiocytes were negative for both KP1 (CD68) and factor XIII.…”
Section: Histopathologic Immunohistochemical and Ultrastructural Fisupporting
confidence: 91%
See 2 more Smart Citations
“…Staining with toluidine blue reveals a marked metachromasia of the histiocytic cells. In accordance with some authors, 53 immunohistochemical studies performed by us showed positive labeling of the histiocytic cells with KP1 (CD68), and factor XIIIa, but S-100 protein and CD1a were negative. In contrast, other investigators 50 found that the histiocytes were negative for both KP1 (CD68) and factor XIII.…”
Section: Histopathologic Immunohistochemical and Ultrastructural Fisupporting
confidence: 91%
“…The disease is very rare and affects almost exclusively women; only 11 patients from 6 different families, [46][47][48][49][50][51] in addition to two sporadic cases, 52,53 have been reported. Indeed, we observed a male patient and his daughter both affected by HPMH (unpublished data).…”
Section: Age Of Onset and Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…No association with paraproteinaemia has been observed. Ten cases – all women – in four families and one sporadic case have been described in the literature 1–6 . An autosomal dominant pattern of inheritance has been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive mucinous histiocytosis is a rare, benign, non‐Langerhans' cell histiocytosis limited to the skin. Ten cases – all women – in four families and one sporadic case have been described in the literature 1–6 . The disorder, characterized by few to numerous flesh‐coloured to red‐brown asymptomatic papules on the face, the hands, the arms and the legs, usually begins in childhood 1–6 .…”
mentioning
confidence: 99%